Leo Strauss on science : thoughts on the relation between natural science and political philosophy - Minkov, Svetozar, 1975- (Albany : State University of New York Press, 2016)
Drawing upon a wealth of previously unpublished archival material, Leo Strauss on Science brings to light the thoughts of Leo Strauss on the problem of science. Introducing us to Strauss's reflections on the meaning and perplexities of the scientific adventure, Svetozar Y. Minkov explores questions such as: Is there a human wisdom independent of science? What is the relation between poetry and mathematics, or between self-knowledge and theoretical physics? And how necessary is it for the human species to exist immutably in order for the classical analysis of human life to be correct? In pursuing these questions, Minkov aims to change the conversation about Strauss, one of the great thinkers of the past century.
Political philosophy and natural science -- Political and psychological preconditions to recovering Socratic science -- The rediscovery of Socratic dialectic: Strauss on Schmitt's concept of the political 2. the fundamental political predicament: Strauss on Plato's laws, book III -- The origin and nature of philosophy -- The natural frame of reference and the possibility of a comprehensive science -- Natural right and history (ch. III) on the origin and nature of philosophy -- Divine revelation and the possibility of science -- Strauss's introduction to Platonic studies in modern times -- Philosophy and revelation -- The foundations and directions of modern philosophy and science -- Science and politics in Strauss's natural right course -- An irony beyond Machiavelli's irony: a reading of the concluding six paragraphs of thoughts on Machiavelli.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
JSTOR
Keywords: Strauss, Leo; Strauss, Leo; Natural history; Political science -- Philosophy; Sciences naturelles; natural sciences; PHILOSOPHY -- Eastern; Natural history; Political science -- Philosophy